2006
DOI: 10.1017/s1466252307001235
|View full text |Cite
|
Sign up to set email alerts
|

Biology of porcine T lymphocytes

Abstract: The present review concentrates on the biological aspects of porcine T lymphocytes. Their ontogeny, subpopulations, localization and trafficking, and responses to pathogens are reviewed. The development of porcine T cells begins in the liver during the first trimester of fetal life and continues in the thymus from the second trimester until after birth. Porcine T cells are divided into two lineages, based on their possession of the alphabeta or gammadelta T-cell receptor. Porcine alphabeta T cells recognize an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 52 publications
(41 citation statements)
references
References 180 publications
(378 reference statements)
4
37
0
Order By: Relevance
“…This is consistent with the established properties of porcine CD4 + CD8 + T cells, which are unique compared to other mammalian hosts in their high frequency outside the thymus [32]. The porcine CD4 + CD8 + population contains memory T helper cells that recognize antigens in an MHC class II-restricted manner [33]. The CD4 + CD8 + are multifunctional, as they express perforin and mediate antigen-specific cytolytic activity against virus-infected target cells [34,35].…”
Section: Discussionsupporting
confidence: 83%
“…This is consistent with the established properties of porcine CD4 + CD8 + T cells, which are unique compared to other mammalian hosts in their high frequency outside the thymus [32]. The porcine CD4 + CD8 + population contains memory T helper cells that recognize antigens in an MHC class II-restricted manner [33]. The CD4 + CD8 + are multifunctional, as they express perforin and mediate antigen-specific cytolytic activity against virus-infected target cells [34,35].…”
Section: Discussionsupporting
confidence: 83%
“…The authors concluded that the vaccine was able to induce a systemic SIV-specific memory T cell response. We observed similar results by MP-FCM in that the inactivated vaccine could prime the CD4+CD8+ T cell subset, a population of T cells that have been demonstrated to be memory T cells in swine (Zuckermann and Husmann, 1996;Charerntantanakul and Roth, 2007). Although we did not measure antigen-specific proliferation, which is often used for evaluating antigenspecific recall responses, we did evaluate changes in expression of intracellular IFN-␥ (Th1 cytokine) and IL-10 (Th2 cytokine), both of which are produced in response to specific recall antigens.…”
Section: Antigen Group Control Vaccinatedsupporting
confidence: 72%
“…CD4/CD8 double-positive (DP) lymphocytes were found to increase gradually in proportion with age (30-55% by 3 years of age) and were able to proliferate in response to stimulation with recall viral antigen consistent with the hypothesis that this population in swine includes memory/effector T cells [52,173,177,248,249] [152]. Accordingly, after mitogen activation CD4 + 2E3 + T cells express high levels of IL-2 mRNA, but only traces of IFN-or IL-4 mRNA.…”
Section: Cd4supporting
confidence: 61%
“…MAb anti-CD45 (or leukocyte common antigen) were based on their broad reactivity patterns with lymphoid and myeloid cells and their ability to immunoprecipitate three polypeptides with an apparent MW of 226, 210 and 190 kDa whereas mAb anti-CD45R were based on their restricted reactivity against lymphoid and myeloid target cells, and their ability to immunoprecipitate either two polypeptides with an apparent molecular weight of 226 and 210 kDa or a single polypeptide with an apparent molecular weight of 210 kDa [52,247].…”
Section: Cd45 and Cd45rmentioning
confidence: 99%